1997
DOI: 10.1097/00001756-199701200-00027
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine modulates the neurotoxic effect of β-amyloid protein(25–35) in hippocampal cultures

Abstract: Two major features of Alzheimer's disease (AD) are beta-amyloid protein (beta AP) deposition and a severe cholinergic deficit. An association between the two is suggested by the negative correlation found between cigarette smoking and AD. We sought to investigate this further by examining the effects of acute and chronic nicotine exposure on beta AP-induced neuronal loss in rat hippocampal cultures. Nicotine was found to attenuate the neurotoxicity of higher concentrations of beta AP(25-35), an effect which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 13 publications
0
46
0
1
Order By: Relevance
“…35 Nicotinic receptor stimulation, especially α7nAChR activation by treatment with nicotine as an example, protects neuron against Aβ-induced cytotoxicity both in cortical and hippocampal neurons. 36,37 Furthermore, we here demonstrated described with some modifications. 14 Briefly, the brain tissues were cleaned free of meningeal tissue, minced and mechanically dissociated by passage through a flame-polished Pasteur pipette.…”
Section: Methodsmentioning
confidence: 91%
“…35 Nicotinic receptor stimulation, especially α7nAChR activation by treatment with nicotine as an example, protects neuron against Aβ-induced cytotoxicity both in cortical and hippocampal neurons. 36,37 Furthermore, we here demonstrated described with some modifications. 14 Briefly, the brain tissues were cleaned free of meningeal tissue, minced and mechanically dissociated by passage through a flame-polished Pasteur pipette.…”
Section: Methodsmentioning
confidence: 91%
“…More recent studies have shown that nicotine can protect against toxicity induced by ␤-amyloid [A␤, the amyloidogenic fragment of the amyloid precursor protein, (APP)], the primary component of neuritic plaques found in the brains of patients with AD (Kihara et al, 1997(Kihara et al, , 1998Zamani et al, 1997) (Table 1). Interestingly, both ␣-bungarotoxin sensitive and insensitive nAChRs are effective in these in vitro models.…”
Section: Neuronal Nachrs and Neuroprotectionmentioning
confidence: 99%
“…However, in many cases, the neuroprotective effects of nicotine can be blocked by mecamylamine or dihydro-␤-erythroidine, antagonists relatively selective for the high-affinity subfamily (mainly ␣4/␤2 subunit-containing) of nAChRs (Kaneko et al, 1997;Zamani et al, 1997;Kihara et al, 1998;Ryan et al, 2001;Laudenbach et al, 2002). The relative contribution of different nAChR subtypes may vary with brain regions such that cortical and striatal neuroprotection by nicotine may be mediated more through ␣4/␤2-type nAChRs (Ryan et al, 2001;Laudenbach et al, 2002), whereas nicotine-induced neuroprotection in the hippocampus and spinal cord may be mediated more through ␣7-type nAChRs (Messi et al, 1997;Dajas-Bailador et al, 2000).…”
Section: And In Vivomentioning
confidence: 99%
“…Just like a number of tetracyclic and carbazole-type compounds, benzofuran inhibits Aβ fibril formation, as a result of the inhibitory properties of these compounds (Howlett et al, 1999). Nicotine can prevent the conformational transition from α-helix to β-sheet (Salomon et al, 1996), and attenuate the neurotoxicity of Aβ through the nicotine receptor (Zamani et al, 1997). Nicotine also enhances the biosynthesis and secretion of transthyretin, which could bind to Aβ peptide to inhibit the formation of amyloid deposition (Tsuzuki et al, 2000).…”
Section: Preventing Aβ Aggregation Formationmentioning
confidence: 99%